PENERAPAN MODEL INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG RANTAI MAKANAN DI KELAS V SD NEGERI BATUESA - Feoh, Pance Yosias; Kota, Martha Khristina; Koroh, Taty Rosiana (Journal of Character and ELementary Education, 2025)
The purpose of this research is to improve the learning outcomes of Grade V Elementary School Students, in the food chain material at SD Negeri Batuesa. This type of research is a class action research with four stages, namely: planning, implementation, test observation and reflection with the subject of this research is class V students totaling 11 people consisting of 4 male students and 7 female students. Data collection is carried out by observation techniques and tests. The data obtained will be further processed and analyzed using qualitative descriptive and quantitative descriptive analyst techniques. The results of the study showed that of the 11 students who completed the first cycle, 7 people (64%). Meanwhile, 4 students (36%) did not complete it. Meanwhile, in the second cycle of 11 students who completed the program, there were 10 students (91%). Meanwhile, only 1 student (9%) was incomplete.